Black and white memories: re-inscription of visual orientalism in embroideries - Jelodar, Esmaeil Zeiny; Noraini Md Yusof, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
In the aftermath of the tragedies of 9/11, the West began to represent the East in a darker way. The western mass media, and the art and literary markets are riddled with visual discourses that consolidate the stereotypical representation of the Orient. One of these visual discourses which strengthen the stereotypes is the portrayals of Eastern women. Almost without exception, the whole mass media use images of eastern veiled women either as victim or lecherous to bolster its East/West demarcation. These sorts of images can be found in some contemporary Muslim women’s works as well. By examining the history of visual orientalism and by studying Marjane Satrapi’s Embroideries (2005), we argue that discourses such as Satrapi’s re-inscribe the visual Orientalism by representing the cliché and stereotypical images of women.